PENDIDIKAN NONGRADASI: PENGAKUANPERBEDAAN INDIVIDU - Sunardi, Sunardi (Jurnal Cakrawala Pendidikan, 2016)
The objective of this research is to develop a non-graded education model In this model, curriculum materials are adapted into sequentially arranged materials. Students are grouped on the bases of their ages, it is possible to have a variety of learning materials and a variety of learning activities within one classroom at the same time. An individual mastery learning approach is implemented. The location of research was in the town of Surakarta. The initial activity was adapting the existing curriculum materials into sequential learning units. The non gradedmodel was tried out in grade 1 of SO Al Firdaus with 62 students (parallel classes). Research results indicate: I)The initial levels of competence of students in a classroom are heterogeneous. 2) In terms of language and sequence of materials, the adapted curriculum package was rated as excellent, but in appropriateness to the levels of development, a few materials for lower grades need to be revised. 3) Teachers and parents agreed on the heterogeneity of classes in schools, but disagreed on the feasibility of multilevel curriculum materials and multi-modality of learning. The two groups also agreed on the low competence of teachers in teaching non-graded classrooms. 4) After one year in progress, the non-graded model showed beneficial for fast and slow learners